Diseño de sistema de riego y monitoreo de variables mediante IOT en los cultivos automatizado con Arduino (2023)
It is proposed to design an automatic irrigation system, which combines free hardware and software solutions, to calculate the humidity of the soil and air since these are vital because they are part of the harvest process.